2008
DOI: 10.1007/s10620-008-0327-6
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori vacA Arrangement and Related Diseases: A Retrospective Study Over a Period of 15 Years

Abstract: Peptic ulcer disease incidence is decreasing. Both s1m1 and s1m2 vacA gene combinations of Helicobacter pylori have been associated with the development of major gastroduodenal diseases. This study assessed whether H. pylori vacA gene arrangement changed over 15 years in a Southern Italy area. H. pylori-positive patients observed in January-June 1989 and January-June 2005 were selected. Histological specimens were retrieved to extract DNA for vacA arrangement characterization (mid-m and peptide signal-s region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Follow-up studies are needed. For example, a study from Italy looked at vacA genotypes over 15 years (from January–June 1989 to January–June 2005) [54]. They reported that although while the prevalence of s1m1 (thought to be more virulent genotype) increased, there was a reduction of peptic ulcer disease in the same area.…”
Section: Vacamentioning
confidence: 99%
“…Follow-up studies are needed. For example, a study from Italy looked at vacA genotypes over 15 years (from January–June 1989 to January–June 2005) [54]. They reported that although while the prevalence of s1m1 (thought to be more virulent genotype) increased, there was a reduction of peptic ulcer disease in the same area.…”
Section: Vacamentioning
confidence: 99%
“…However, s2m1 and s2m2 are considered less toxic because of their inability to form vacuoles [9]. The s1am1 and s1bm1 subtypes are frequently reported in acute gastritis (GIs), peptic ulcer, and gastric cancer patients, while s2m1 and s2m2 have been reported in the gastric ulcer (GU) patients [9, 13]. …”
Section: Introductionmentioning
confidence: 99%
“…Among all genotypic combinations, s1am1 and s1bm1 are considered to be the most virulent and are frequently reported in patients with acute gastritis [19], peptic ulcer [20], and GC [21], followed by s1m2,which is responsible for moderate toxin activity mainly due to the binding capacity of the m2 region with restricted cell types [22]. Although s2m1 and s2m2 are rare (especially s2m1) and are considered the least toxic of the genotypic combinations because of their inability to form vacuoles, they have been reported in patients with DU and GU [20,23].…”
Section: Introductionmentioning
confidence: 99%